The contribution of social communication to projects of rehabilitation of water and sanitation networks: The case of Sedapal Project Lote 3 - Cornejo Alva, Wilfredo (2019)
This paper focus on implementation of communication strategies developed in the Rehabilitation of Potable Water and Sewerage Network Lote 3 project, executed between 2013 and 2014 in the district of Comas, north of Lima-Peru, and belonging to the Servicio de Agua Potable y Alcantarillado de Lima (SEDAPAL), company responsible for water and sewage in Lima. As a result, it could be observed that the implementation of a diagnosis of perceptions, the communication plan and the communication and education products allowed to facilitate the design of messages according to the context of the project, taking into account the speeches of the users against and in favor of the project, as well as the objectives sought by the executing company.